Pseudasthenes, a new genus of ovenbird (Aves: Passeriformes: Furnariidae) - Derryberry, Elizabeth; Claramunt, Santiago; O’quin, Kelly E.; Aleixo, Alexandre; Chesser, R. Terry; Remsen Jr., J. V.; Brumfield, Robb T. (Zootaxa, 2010)
Phylogenetic analysis of the family Furnariidae (Aves: Passeriformes) indicates that the genus Asthenes is polyphyletic, consisting of two groups that are not sister taxa. Pseudasthenes, a new genus of ovenbird, is described for one of these groups. The four species included in the new genus, formerly placed in Asthenes, are P. humicola, P. patagonica, P. steinbachi, and P. cactorum.